Preparation method of self-humidifying membrane electrode of proton exchange membrane fuel cell
By adding COFs materials into the catalytic layer of the proton exchange membrane fuel cell, the problems of water management in the self-humidification membrane electrode are solved, and high-efficiency performance and good performance under low humidity conditions are achieved stability.
Patent Information
- Application Number
- CN202411748918.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing self-humidification membrane electrodes have problems such as internal water management that are prone to imbalance and poor stability of hydrophilic substances, resulting in unstable fuel cell performance.
COFs material is incorporated into the catalytic layer, COFs material is synthesized by the two-phase method, and COFs material is introduced into the membrane electrode catalytic layer to replace part of the perfluorosulfonic acid ionomer and improve water management capabilities and stability.
The efficient performance and good stability of fuel cells under low humidity conditions are achieved, cost reduction, and excellent power density is maintained in a larger humidity range.
Smart Images

Figure CN119419320A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a proton exchange membrane fuel cell membrane electrode, and belongs to the technical field of fuel cell membrane electrodes. Background Art
[0002] Proton exchange membrane fuel cells (PEMFC) occupy an important position in fuel cell technology with its advantages such as high efficiency, low emissions, fast start-up and high power density. They use a proton exchange membrane as an electrolyte, allowing protons to pass through while blocking electrons, thereby generating an electric current in an external circuit. This design makes PEMFC very popular in automotive, portable power and stationary power applications because they can operate at lower operating temperatures and have a long service life and low maintenance requirements.
[0003] Proper humidity ensures that the proton exchange membrane (PEM) is fully hydrated, which is essential for maintaining its proton conduction properties. When the air humidity increases, the water content of the proton exchange membrane can be increased, thereby enhancing the conductivity of the membrane, reducing the impedance on both sides of the membrane, accelerating the hydrogen ion transfer rate within the membrane, and thus increasing the electrochemical reaction rate and improving the output performance of the fuel cell. Especially at high operating voltages, fuel cell performance improves with the increase in the relative humidity of the cathode and anode gases. However, too high or too low humidity can have an adverse effect on PEMFC performance. Too high humidity may lead to "cathode flooding" problems, affecting oxygen transfer and the availability of reaction sites, while too low humidity may lead to "anode dryness", affecting the wetting state of the proton exchange membrane. Therefore, proper humidity control is essential for optimizing the performance of PEMFC.
[0004] The development of self-humidifying membrane electrodes can significantly improve the performance and commercialization potential of proton exchange membrane fuel cells (PEMFCs). Self-humidifying membrane electrodes can remove complex external humidification systems, simplify the battery system structure, and reduce manufacturing costs. Conventional methods for preparing self-humidifying membrane electrodes usually involve introducing hydrophilic materials into the membrane electrode assembly (MEA) to enhance water management capabilities. These methods include adding nano-sized oxide particles such as silicon dioxide (SiO2) or titanium dioxide (TiO2) to the catalyst layer, which can adsorb and retain water; using hydrophilic polymers such as polyvinyl alcohol (PVA) or carboxymethyl cellulose (CMC) to improve the water retention of the catalyst layer; and optimizing water transport and distribution by adjusting the microstructure of the catalyst layer, such as increasing porosity or changing pore size distribution. These technologies can reduce the dependence on external humidification systems and improve the performance and durability of fuel cells under different environmental conditions. Although the above methods are helpful to improve the performance of fuel cells under different humidity conditions, they also have some disadvantages, including the addition of hydrophilic substances may lead to imbalance of water management inside the battery, increase ohmic resistance and reduce conductivity; stability and durability issues of hydrophilic substances, resulting in performance degradation during long-term operation; increased cost and preparation complexity, as well as possible structural design limitations, all of which limit the widespread application and commercialization of these methods. Therefore, further research and innovation are needed to optimize these methods to overcome their limitations and improve the overall performance and reliability of fuel cells. Summary of the invention
[0005] The present invention aims to solve the technical problems of the existing self-humidifying membrane electrode, such as the imbalance of internal water management and the poor stability and durability of hydrophilic substances, which lead to poor battery performance, and provide a method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell. The prepared electrode is a new membrane electrode with COFs material doped in the catalyst layer.
[0006] The method for preparing the self-humidifying membrane electrode of the proton exchange membrane fuel cell of the present invention is carried out according to the following steps:
[0007] 1. Two-phase synthesis of COFs materials:
[0008] (1) Weigh 0.1-1 mmol of 2,4,6-triformylpyrogallol, dissolve it in 20-200 mL of octanoic acid, and disperse it by ultrasonic for 30-120 min to form a solution A;
[0009] (2) Weigh 0.15-1.5 mmol of 2,5-diaminobenzenesulfonic acid and dissolve it in 30-300 mL of deionized water, and disperse it by ultrasonic for 30-120 min to form a solution B;
[0010] (3) Then, solution A is added dropwise into solution B, and solution A will float on top of solution B to form a two-phase separated liquid phase reaction system; the mixture is allowed to stand at room temperature for 3 to 7 days, and after the reaction is completed, the lower liquid phase is separated, and the liquid phase is evaporated in a water bath at 60 to 80° C. for 6 to 10 hours, and then freeze-dried to obtain a COFs material, which is a reddish brown solid;
[0011] 2. Preparation of membrane electrode catalyst layer slurry:
[0012] (1) Conventional catalytic layer slurry: Pt / C catalyst and perfluorosulfonic acid ionomer solution are dispersed in an organic solvent at room temperature; wherein the dry weight of perfluorosulfonic acid and the mass ratio of the carbon support of the Pt / C catalyst, i.e., I / C, is (0.6-0.9):1, the dry weight of perfluorosulfonic acid is recorded as M, and the mass of the Pt / C catalyst is recorded as N; after uniform dispersion, a conventional catalytic layer slurry a is obtained;
[0013] (2) Self-humidifying catalytic layer slurry containing COFs material: Weigh a Pt / C catalyst with a mass of N, a COFs material with a mass of L=(0.1~0.5)M, and a perfluorosulfonic acid solution with a dry weight of ML; then disperse the Pt / C catalyst, COFs material, and perfluorosulfonic acid solution in an organic solvent, and after uniform dispersion, obtain a self-humidifying catalytic layer slurry b containing COFs material.
[0014] 3. Preparation of membrane electrode:
[0015] (1) Preparation of anode catalyst layer: Slurry a is loaded into an ultrasonic spraying device, and the proton exchange membrane is adsorbed on the adsorption platform of the ultrasonic spraying device. The temperature of the adsorption platform is controlled at 70-90°C, and slurry a is evenly sprayed onto the proton exchange membrane until the Pt loading is 0.025-0.2 mg / cm 2 , this surface is used as the anode surface;
[0016] (2) Preparation of cathode surface: Slurry b was loaded into ultrasonic spraying equipment, and the proton exchange membrane sprayed with slurry a was adsorbed on the adsorption platform of the ultrasonic spraying equipment. The temperature of the adsorption platform was controlled at 70-90°C, and slurry b was evenly sprayed on the other side of the proton exchange membrane until the Pt spraying loading was 0.1-0.4 mg / cm 2 This surface is used as the cathode surface to obtain a self-humidifying membrane electrode.
[0017] Furthermore, the mass percentage purity of the 2,4,6-triformylpyrogallol in step 1 is ≥95%, and the mass percentage purity of the 2,5-diaminobenzenesulfonic acid is ≥98%.
[0018] Furthermore, the Pt / C catalyst described in step 2 is JM 20% Pt / C catalyst, JM 40% Pt / C catalyst, JM 50% Pt / C catalyst, JM 60% Pt / C catalyst, TKK 20% Pt / C catalyst, TKK 40% Pt / C catalyst, TKK 50% Pt / C catalyst or TKK 60% Pt / C catalyst.
[0019] Furthermore, the perfluorosulfonic acid ionomer solution in step 2 is DuPont D520, Aquivion D79-25BS, AGC IC100 or AGC IC154.
[0020] Furthermore, the organic solvent described in step 2 is a mixture of isopropanol and water in a mass ratio of (0.2-5):1.
[0021] Furthermore, the dispersion method described in step 2 is high-speed shear dispersion, the equipment model is OuHorA25, and the dispersion is carried out at 15000-20000 r / min for 30-60 min.
[0022] Furthermore, the proton exchange membrane described in step three includes Chemours Nafion 115, Nafion 117, Nafion 212, Gore 8μm, Gore 12μm or Gore 15μm.
[0023] The advantages of the method for preparing the self-humidifying membrane electrode of the proton exchange membrane fuel cell of the present invention are as follows:
[0024] (1) The COFs material is synthesized by a two-phase method, and its synthesis expression is:
[0025]
[0026] Compared with the solvent thermal method used in the traditional COFs synthesis, the liquid phase synthesis method of the present invention can synthesize COFs quickly and efficiently under milder conditions while maintaining high crystallinity and controllable solubility; the liquid phase synthesis method does not require high temperature and high pressure conditions, has lower energy consumption, and has higher crystallinity and specific surface area; in addition, the liquid phase synthesis method also avoids excessive use of organic solvents and is more environmentally friendly. In general, the liquid phase synthesis method shows obvious advantages over the solvent thermal method in terms of environmental friendliness, energy consumption, synthesis efficiency and crystallinity.
[0027] (2) The introduction of additional metal elements into the catalyst layer of the proton exchange membrane fuel cell may lead to metal ion contamination, affect the performance of the catalyst layer, reduce the ionic conductivity and stability of the membrane, accelerate the chemical degradation of the membrane, affect the oxygen reduction performance of the catalyst, and cause the battery performance to decay, thereby having a negative impact on the overall performance and life of the battery. COFs materials do not contain metal elements. Compared with nano-sized water-retaining oxide TiO2 and hygroscopic MOF materials, they avoid the introduction of metal elements into the catalyst layer, thereby being able to exhibit excellent stability. In addition, compared with hydrophilic polymers such as polyvinyl alcohol (PVA) or carboxymethyl cellulose (CMC) and SiO2, the pores of COFs materials can be modified with proton-transferring groups, such as -SO 3- and -COOH, etc., eliminating the negative effects of PVA, CMC and SiO2 themselves as electrical insulating materials on battery performance. The highly ordered porous structure, adjustable pore size and chemical functionality of COFs materials enable COFs to provide excellent gas diffusion performance and proton conductivity, and can accurately adjust the intrapore environment to enhance the ion exchange capacity. The COFs material (NUS-9) used in the present invention is synthesized by a simple two-phase method and has a two-dimensional nanosheet structure. This structure has abundant rigid pores with a pore size of about 1.4nm and a theoretical ion exchange capacity (IEC) of 3.4mmol / g. Its highly ordered structure provides an efficient proton transport path, and has a high concentration of proton donors (sulfonic acid groups) with high proton conductivity. The crystal structure and rigid nanochannels of NUS-9 can effectively fix water molecules through capillary forces, thereby maintaining the hydration degree of the catalyst layer even at low humidity. In addition, the highly confined water microenvironment and spatially arranged proton donor sites in NUS-9 work together to efficiently transfer protons via the Grotthuss mechanism even at low humidity, thereby optimizing the battery performance at low humidity.
[0028] (3) The perfluorosulfonic acid ionomers currently used in the preparation of the catalyst layer of proton exchange membrane fuel cells are expensive and have a complicated production process. The present invention uses COFs materials to partially replace perfluorosulfonic acid ionomers. The high chemical and thermal stability of COFs enables them to maintain performance even under harsh battery operating conditions, and their easy modification makes it possible to introduce specific functional groups. The sulfonate groups in their pores can maintain efficient proton transmission over a wide range of humidity. Therefore, the COFs material also plays the role of a perfluorosulfonic acid ionomer while absorbing water.
[0029] The COFs material used in the present invention is synthesized by a simple two-phase method and has a two-dimensional nanosheet structure. This structure has abundant rigid pores with a pore size of about 1.4 nm, and can maintain capillary attraction to water at low humidity. On the other hand, the pores of the COFs material contain sulfonate groups that can conduct protons, and maintain efficient proton transfer capabilities at low humidity. In addition, replacing part of perfluorosulfonic acid with COFs also saves costs and has excellent economic benefits. The results of single-cell performance tests show that the self-humidifying membrane electrode of the present invention exhibits better performance and good stability than conventional membrane electrodes under low humidity conditions, and exhibits better power density than the control sample over a larger humidity range. The peak power density of the self-humidifying membrane electrode of the present invention at 20% relative humidity is 756.3 mW / cm 2 The peak power density at 50% relative humidity is 437.8~879.7mW / cm 2 The peak power density at 40% relative humidity is 474.6~629.7mW / cm 2 .
[0030] The preparation method of the present invention is simple, and the prepared self-humidifying membrane electrode has a wide range of application values, which is helpful to further promote the commercial development of self-humidifying fuel cell vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Water contact angle test diagram of the membrane electrode of Example 1 and Comparative Example 1;
[0032] Figure 2 Battery performance diagram of the membrane electrode of Example 1 and Comparative Example 1 at 20% relative humidity;
[0033] Figure 3 Cell power density diagram of membrane electrodes of Examples 2 to 5 and Comparative Example 2 at 50% relative humidity;
[0034] Figure 4 Battery performance diagram of the membrane electrodes of Examples 6 to 9 and Comparative Example 3 at 40% relative humidity. Specific implementation methods
[0036] In order to make the implementation details and operation capabilities of the present invention clearly understood by those skilled in the art, the present invention is described below through multiple examples. It should be pointed out that for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent of the present invention shall be subject to the attached claims.
[0037] Embodiment 1: The method for preparing the self-humidifying membrane electrode of the proton exchange membrane fuel cell of this embodiment is carried out according to the following steps:
[0038] 1. Two-phase synthesis of COFs materials:
[0039] (1) Weigh 0.1 mmol of 2,4,6-triformylpyrogallol with a mass percent purity of 98%, dissolve it in 20 mL of octanoic acid, and disperse it by ultrasonic for 30 min;
[0040] (2) Weigh 0.15 mmol of 2,5-diaminobenzenesulfonic acid with a mass percent purity of 99% and dissolve it in 30 mL of deionized water, and disperse it by ultrasonic for 30 min to form solution B;
[0041] (3) Then, solution A is added dropwise into solution B, and solution A will float on top of solution B to form a two-phase separated liquid phase reaction system; the reaction is allowed to stand at room temperature for 3 days until it is complete, and the lower liquid phase is separated, and the liquid phase is evaporated in a 60°C water bath for 8 hours, and then freeze-dried to obtain a COFs material, which is a reddish brown solid;
[0042] 2. Preparation of membrane electrode catalyst layer slurry:
[0043] (1) Conventional catalytic layer slurry: 0.2 g of JM 40% Pt / C catalyst was weighed, and then the Pt / C catalyst and AGCIC100 solution were dispersed in a mixture of 25 g of isopropanol and water in a mass ratio of 2:1 at room temperature according to a mass ratio of dry weight of perfluorosulfonic acid to carbon support of the Pt / C catalyst, i.e., I / C of 0.9:1, wherein the dry weight of perfluorosulfonic acid M = 0.108 g, and dispersed for 30 min using a high-speed shear emulsifier OuHorA2 at a speed of 20,000 r / min to obtain a conventional catalytic layer slurry a;
[0044] (2) Self-humidifying catalytic layer slurry containing COFs material: 0.2 g of JM 40% Pt / C catalyst was weighed, and then 0.027 g of COFs material was weighed, and then 0.081 g of perfluorosulfonic acid solution was weighed, and then the Pt / C catalyst, COFs material, and perfluorosulfonic acid solution were dispersed in a mixture of 25 g of isopropanol and water in a mass ratio of 1:1, and dispersed for 30 minutes using a high-speed shear emulsifier OuHor A2 at a speed of 20,000 r / min to obtain a self-humidifying catalytic layer slurry b containing COFs material.
[0045] 3. Preparation of membrane electrode:
[0046] (1) Preparation of anode catalyst layer: Slurry a was loaded into an ultrasonic spraying device, and Nafion 115 membrane was adsorbed on the adsorption platform of the ultrasonic spraying device. The temperature of the adsorption platform was controlled at 75°C, and slurry a was evenly sprayed onto the proton exchange membrane until the Pt loading reached 0.1 mg / cm 2 , this surface is used as the anode surface;
[0047] (2) Preparation of cathode surface: Slurry b was loaded into ultrasonic spraying equipment, and the proton exchange membrane sprayed with slurry a was adsorbed on the adsorption platform of the ultrasonic spraying equipment. The temperature of the adsorption platform was controlled at 75°C, and slurry b was evenly sprayed on the other side of the proton exchange membrane until the Pt spraying loading reached 0.2 mg / cm 2 This surface is used as the cathode surface to obtain a self-humidifying membrane electrode.
[0048] The structural unit of the COFs material prepared in step 1 of Example 1 is:
[0049] The COFs material is connected by covalent bonds and has a very stable rigid six-membered ring structure. The pore diameter is about 1.4nm, which can provide sufficient capillary force to firmly absorb water even in low humidity environments. In addition, the sulfonate groups in the pores can also conduct protons under low humidity, avoiding the problem of reduced conductivity caused by the addition of hydrophilic materials.
[0050] Comparative Example 1: This comparative example is different from Example 1 in that the cathode surface in step 3 is also sprayed with slurry a, and the Pt spraying loading is 0.2 mg / cm 2 , other steps and parameters are the same as those in Example 1 to obtain a conventional membrane electrode.
[0051] The self-humidifying membrane electrode prepared in Example 1 and the conventional membrane electrode prepared in Comparative Example 1 were tested for water contact angles. The water contact angle photos obtained are shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the water contact angle of the self-humidifying membrane electrode in Example 1 is 115.4°, while the water contact angle of the conventional membrane electrode in Comparative Example 1 is 133.5°. The water contact angle of the self-humidifying membrane electrode in Example 1 is significantly lower than that of the conventional membrane electrode in Comparative Example 1, which proves that the hydrophilicity of the self-humidifying membrane electrode in Example 1 is significantly enhanced, which indirectly verifies its water retention effect during operation in a low humidity environment.
[0052] Single cells were assembled using the self-humidifying membrane electrode prepared in Example 1 and the conventional membrane electrode prepared in Comparative Example 1, respectively. The specific method was as follows: the anode end plate was placed on a desktop, a stud was inserted, and a current collecting plate, an anode plate, a gasket, an anode gas diffusion layer Avcarb MB30, a membrane electrode, a cathode gas diffusion layer Avcarb MB30, a gasket, a cathode plate, a current collector and a cathode end plate were stacked in sequence, nuts were screwed on the studs, and they were tightened in diagonal order. The tightening pressure increased by 20-30-40kgf.cm. After assembly, it was connected to a fuel cell test system for electrochemical performance testing.
[0053] The polarization performance in a H2 / O2 environment was tested using a Scribner 850e membrane electrode test system at 80°C, 100kPa back pressure, and 20% relative humidity. Both H2 and O2 were at a constant flow rate of 0.5L / min. Cell performance of the self-humidifying membrane electrode prepared in Example 1 and the conventional membrane electrode prepared in Comparative Example 1 at 20% relative humidity Figure 2 As shown, from Figure 2 It can be seen that with oxygen as the oxidant, the peak power density of the self-humidifying membrane electrode of Example 1 is 756.3 mW / cm 2 The peak power density of comparative example 1 is 592.3 mW / cm 2 The performance of the self-humidifying membrane electrode of Example 1 far exceeds that of the conventional membrane electrode of Comparative Example 1, which proves the performance advantage of the self-humidifying membrane electrode of Example 1 under low humidity.
[0054] Example 2: The method for preparing the self-humidifying membrane electrode of the proton exchange membrane fuel cell of this example is carried out according to the following steps:
[0055] 1. Two-phase synthesis of COFs materials:
[0056] (1) Weigh 0.5 mmol of 2,4,6-triformylpyrogallol with a mass percent purity of 98%, dissolve it in 100 mL of octanoic acid, and disperse it by ultrasonic for 60 minutes to form a solution A;
[0057] (2) Weigh 0.75 mmol of 2,5-diaminobenzenesulfonic acid with a mass percent purity of 99% and dissolve it in 150 mL of deionized water, and disperse it by ultrasonic for 60 minutes to form a solution B;
[0058] (3) Then, solution A is added dropwise into solution B, and solution A will float on top of solution B to form a two-phase separated liquid phase reaction system; the reaction is allowed to stand at room temperature for 5 days until it is complete, and the lower liquid phase is separated, and the liquid phase is evaporated in an 80°C water bath for 8 hours, and then freeze-dried to obtain a COFs material, which is a reddish brown solid;
[0059] 2. Preparation of membrane electrode catalyst layer slurry:
[0060] (1) Conventional catalytic layer slurry: 0.2 g of TKK 50% Pt / C catalyst was weighed, and then TKK 50% Pt / C catalyst and Aquivion D79-25BS solution were dispersed in a mixture of 25 g isopropanol and water in a mass ratio of 1.2:1 at room temperature according to a mass ratio of dry weight of perfluorosulfonic acid to carbon support of Pt / C catalyst, i.e., I / C of 0.8:1, wherein the dry weight of perfluorosulfonic acid M = 0.08 g, and dispersed for 45 min using a high-speed shear emulsifier OuHorA2 at a rotation speed of 20,000 r / min to obtain conventional catalytic layer slurry a;
[0061] (2) Self-humidifying catalytic layer slurry containing COFs material: Weigh 0.2 g of TKK 50% Pt / C catalyst, then weigh 0.04 g of COFs material, and then weigh 0.04 g of perfluorosulfonic acid solution with a dry weight. Then, disperse the Pt / C catalyst, COFs material, and perfluorosulfonic acid solution in a mixture of 25 g of isopropanol and water in a mass ratio of 1.5:1, and use a high-speed shear emulsifier OuHorA2 to disperse for 30 minutes at a speed of 20,000 r / min to obtain a self-humidifying catalytic layer slurry b containing COFs material.
[0062] 3. Preparation of membrane electrode:
[0063] (1) Preparation of anode catalyst layer: Slurry a was loaded into an ultrasonic spraying device, and Nafion 212 membrane was adsorbed on the adsorption platform of the ultrasonic spraying device. The temperature of the adsorption platform was controlled at 80°C. Slurry a was evenly sprayed onto the proton exchange membrane until the Pt loading reached 0.05 mg / cm 2 , this surface is used as the anode surface;
[0064] (2) Preparation of cathode surface: Slurry b was loaded into ultrasonic spraying equipment, and the proton exchange membrane sprayed with slurry a was adsorbed on the adsorption platform of the ultrasonic spraying equipment. The temperature of the adsorption platform was controlled at 80°C, and slurry b was evenly sprayed on the other side of the proton exchange membrane until the Pt spraying loading reached 0.1 mg / cm 2 This surface is used as the cathode surface to obtain a self-humidifying membrane electrode.
[0065] Example 3: This example is different from Example 2 in that the mass of the TKK 50% Pt / C catalyst in step 2 (2) is 0.2 g, the mass of the COFs material is 0.4 M, and the dry weight of the perfluorosulfonic acid solution is 0.6 M. The other steps and parameters are the same as those in Example 2.
[0066] Example 4: This example is different from Example 2 in that the mass of the TKK 50% Pt / C catalyst in step 2 (2) is 0.2 g, the mass of the COFs material is 0.3 M, the dry weight of the perfluorosulfonic acid solution is 0.7 M, and the other steps and parameters are the same as in Example 2.
[0067] Example 5: This example is different from Example 2 in that the mass of the TKK 50% Pt / C catalyst in step 2 (2) is 0.2 g, the mass of the COFs material is 0.2 M, the dry weight of the perfluorosulfonic acid solution is 0.8 M, and the other steps and parameters are the same as in Example 2.
[0068] Comparative Example 2: This comparative example is different from Example 2 in that the cathode surface in step 3 is also sprayed with slurry a, and the Pt spraying loading is 0.1 mg / cm2 , other steps and parameters are the same as those in Example 2 to obtain a conventional membrane electrode.
[0069] The membrane electrodes prepared in Examples 2 to 5 and Comparative Example 2 and the diffusion layer of SGL 28BC are assembled into a single cell. The specific method is as follows: place the anode end plate on a desktop, insert a stud, and stack the current collecting plate, anode plate, gasket, anode gas diffusion layer SGL 28BC, membrane electrode, cathode gas diffusion layer SGL 28BC, gasket, cathode plate, current collector and cathode end plate in sequence, screw nuts on the studs, tighten them in diagonal order, and increase the tightening pressure by 20-30-40kgf.cm. After assembly, connect it to the fuel cell test system for electrochemical performance testing.
[0070] The polarization performance in a H2 / Air environment was tested using a Scribner 850e membrane electrode test system at 80°C, 100kPa back pressure, and 50% relative humidity. The H2 and air flow rates were 0.5L / min and 2L / min, respectively. Figure 3 As shown, from Figure 3 It can be seen that the peak power densities of Examples 2-5 are 437.8 mW / cm 2 、637.9mW / cm 2 、896.8mW / cm 2 、879.7mW / cm 2 The peak power density of comparative example 2 is 375.1 mW / cm 2 The performance of the self-humidifying membrane electrode far exceeds that of the conventional membrane electrode, which proves the performance advantage of the self-humidifying membrane electrode of Examples 2 to 5 under low humidity.
[0071] Example 6: The method for preparing the self-humidifying membrane electrode of the proton exchange membrane fuel cell of this embodiment is carried out according to the following steps:
[0072] 2. Two-phase synthesis of COFs materials:
[0073] (1) Weigh 1 mmol of 2,4,6-triformylpyrogallol with a mass percent purity of 98%, dissolve it in 200 mL of octanoic acid, and disperse it by ultrasonic for 120 min to form a solution A;
[0074] (2) Weigh 1.5 mmol of 2,5-diaminobenzenesulfonic acid with a mass percent purity of 99% and dissolve it in 300 mL of deionized water, and disperse it by ultrasonic for 120 min to form solution B;
[0075] (3) Then, solution A is added dropwise into solution B, and solution A will float on top of solution B to form a two-phase separated liquid phase reaction system; the reaction is allowed to stand at room temperature for 7 days until it is finished, and the lower liquid phase is separated, and the liquid phase is evaporated in an 80°C water bath for 8 hours, and then freeze-dried to obtain a COFs material, which is a reddish brown solid;
[0076] 2. Preparation of membrane electrode catalyst layer slurry:
[0077] (1) Conventional catalytic layer slurry: 0.2 g of JM 60% Pt / C catalyst was weighed, and then the Pt / C catalyst and DuPont D520 solution were dispersed in a mixture of 25 g of isopropanol and water in a mass ratio of 1:1 at room temperature at a mass ratio of dry weight of perfluorosulfonic acid to carbon support of the Pt / C catalyst, i.e., I / C of 0.6:1, wherein the dry weight of perfluorosulfonic acid M = 0.048 g, and dispersed for 30 min using a high-speed shear emulsifier OuHorA2 at a rotation speed of 20,000 r / min to obtain a conventional catalytic layer slurry a;
[0078] (2) Self-humidifying catalytic layer slurry containing COFs material: Weigh 0.2 g of JM 40% Pt / C catalyst, then weigh 0.012 g of COFs material, and then weigh 0.036 g of perfluorosulfonic acid solution with a dry weight. Then, disperse the Pt / C catalyst, COFs material, and perfluorosulfonic acid solution in a mixture of 25 g of isopropanol and water in a mass ratio of 1:1, and use a high-speed shear emulsifier OuHorA25 to disperse for 30 minutes at a speed of 20,000 r / min to obtain a self-humidifying catalytic layer slurry b containing COFs material.
[0079] 3. Preparation of membrane electrode:
[0080] (1) Preparation of anode catalyst layer: Slurry a was loaded into an ultrasonic spraying device, and a Gore 12 μm membrane was adsorbed on the adsorption platform of the ultrasonic spraying device. The temperature of the adsorption platform was controlled at 75 °C, and slurry a was evenly sprayed onto the proton exchange membrane until the Pt loading reached 0.1 mg / cm 2 , this surface is used as the anode surface;
[0081] (2) Preparation of cathode surface: Slurry b was loaded into ultrasonic spraying equipment, and the proton exchange membrane sprayed with slurry a was adsorbed on the adsorption platform of the ultrasonic spraying equipment. The temperature of the adsorption platform was controlled at 75°C, and slurry b was evenly sprayed on the other side of the proton exchange membrane until the Pt spraying loading reached 0.2 mg / cm 2 This surface is used as the cathode surface to obtain a self-humidifying membrane electrode.
[0082] Example 7: This example differs from Example 6 in that in step 2 (1), the I / C ratio is changed from 0.6:1 to 0.7:1, the dry weight of perfluorosulfonic acid M=0.056 g, and the remaining steps and parameters are the same as those of Example 6.
[0083] Example 8: This example differs from Example 6 in that in step 2 (1), the I / C ratio is changed from 0.6:1 to 0.8:1, the dry weight of perfluorosulfonic acid M=0.064 g, and the remaining steps and parameters are the same as those of Example 6.
[0084] Example 9: This example differs from Example 6 in that in step 2 (1), the I / C ratio is changed from 0.6:1 to 0.9:1, the dry weight of perfluorosulfonic acid M=0.072 g, and the remaining steps and parameters are the same as those of Example 6.
[0085] Comparative Example 3: This comparative example is different from Example 6 in that the cathode surface in step 3 is also sprayed with slurry a, and the Pt spraying loading is 0.2 mg / cm 2 , other steps and parameters are the same as those in Example 6 to obtain a conventional membrane electrode.
[0086] The membrane electrodes prepared in Examples 6 to 9 and Comparative Example 3 and the Toray XGL-R-055 diffusion layer were assembled into a single cell. The specific method was as follows: the anode end plate was placed on a desktop, a stud was inserted, and the current collector, anode plate, gasket, anode gas diffusion layer Toray XGL-R-055, membrane electrode, cathode gas diffusion layer Toray XGL-R-055, gasket, cathode plate, current collector and cathode end plate were stacked in sequence, nuts were screwed on the studs, and they were tightened in diagonal order. The tightening pressure was increased by 20-30-40kgf.cm. After the assembly was completed, it was connected to the fuel cell test system for electrochemical performance testing.
[0087] The polarization performance in a H2 / Air environment was tested using a Scribner 850e membrane electrode test system at 80°C, 100kPa back pressure, and 40% relative humidity. The H2 and air flow rates were 0.5L / min and 2L / min, respectively. Figure 4 As shown, from Figure 4 It can be seen that the peak power densities of Examples 6-9 are 629.7 mW / cm 2 、573.9mW / cm 2 、485.8mW / cm 2 、474.6mW / cm 2 The peak power density of comparative example 3 is 442.2 mW / cm 2 The performance of the self-humidifying membrane electrode far exceeds that of the conventional membrane electrode, which proves the performance advantage of the self-humidifying membrane electrode of Examples 6 to 9 under low humidity.
Claims
1. A method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell, characterized in that The method proceeds as follows:
1. Two-phase synthesis of COFs materials: (1) Weigh 0.1-1 mmol of 2,4,6-triformylpyrogallol, dissolve it in 20-200 mL of octanoic acid, and disperse it by ultrasonic for 30-120 min to form a solution A; (2) Weigh 0.15-1.5 mmol of 2,5-diaminobenzenesulfonic acid and dissolve it in 30-300 mL of deionized water, and disperse it by ultrasonic for 30-120 min to form a solution B; (3) Then, solution A is added dropwise into solution B, and solution A will float on top of solution B to form a two-phase separated liquid phase reaction system; the reaction is allowed to stand at room temperature for 3 to 7 days, and after the reaction is completed, the lower liquid phase is separated, and the liquid phase is evaporated in a water bath at 60 to 80° C. for 6 to 10 hours, and then freeze-dried to obtain a COFs material, which is a reddish brown solid; 2. Preparation of membrane electrode catalyst layer slurry: (1) Conventional catalytic layer slurry: Pt / C catalyst and perfluorosulfonic acid ionomer solution are dispersed in an organic solvent at room temperature; wherein the dry weight of perfluorosulfonic acid and the mass ratio of the carbon support of the Pt / C catalyst, i.e., I / C, is 0.6-0.9:1, the dry weight of perfluorosulfonic acid is recorded as M, and the mass of the Pt / C catalyst is recorded as N; after uniform dispersion, conventional catalytic layer slurry a is obtained; (2) Self-humidifying catalytic layer slurry containing COFs material: weigh a Pt / C catalyst with a mass of N, a COFs material with a mass of L=(0.1-0.5)M, and a perfluorosulfonic acid solution with a dry weight of ML; then disperse the Pt / C catalyst, COFs material, and perfluorosulfonic acid solution in an organic solvent, and after uniform dispersion, obtain a self-humidifying catalytic layer slurry b containing COFs material; 3. Preparation of membrane electrode: (1) Preparation of anode catalyst layer: Slurry a is loaded into an ultrasonic spraying device, and the proton exchange membrane is adsorbed on the adsorption platform of the ultrasonic spraying device. The temperature of the adsorption platform is controlled at 70-90°C, and slurry a is evenly sprayed onto the proton exchange membrane until the Pt loading is 0.025-0.2 mg / cm 2 , this surface is used as the anode surface; (2) Preparation of cathode surface: Slurry b was loaded into ultrasonic spraying equipment, and the proton exchange membrane sprayed with slurry a was adsorbed on the adsorption platform of the ultrasonic spraying equipment. The temperature of the adsorption platform was controlled at 70-90°C, and slurry b was evenly sprayed on the other side of the proton exchange membrane until the Pt spraying loading was 0.1-0.4 mg / cm 2 This surface is used as the cathode surface to obtain a self-humidifying membrane electrode.
2. The method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell according to claim 1, characterized in that: The mass percentage purity of the 2,4,6-triformylpyrogallol described in step 1 is ≥95%, and the mass percentage purity of the 2,5-diaminobenzenesulfonic acid is ≥98%.
3. The method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell according to claim 1 or 2, characterized in that: The Pt / C catalyst described in step 2 is JM 20% Pt / C catalyst, JM 40% Pt / C catalyst, JM50% Pt / C catalyst, JM 60% Pt / C catalyst, TKK 20% Pt / C catalyst, TKK 40% Pt / C catalyst, TKK50% Pt / C catalyst or TKK 60% Pt / C catalyst.
4. The method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell according to claim 1 or 2, characterized in that: The perfluorosulfonic acid ionomer solution in step 2 is DuPont D520, Aquivion D79-25BS, AGCIC100 or AGC IC154.
5. The method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell according to claim 1 or 2, characterized in that: The organic solvent described in step 2 is a mixture of isopropanol and water in a mass ratio of (0.2-5):
1.
6. The method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell according to claim 1 or 2, characterized in that: The dispersion method described in step 2 is high-speed shear dispersion, which is dispersed at 15000-20000 r / min for 30-60 min.
7. The method for preparing a self-humidifying membrane electrode for a proton exchange membrane fuel cell according to claim 1 or 2, characterized in that: The proton exchange membrane described in step 3 includes Chemours Nafion 115, Nafion 117, Nafion 212, Gore 8 μm, Gore 12 μm or Gore 15 μm.
Citation Information
Patent Citations
Method for preparing membrane electrode capable of improving low-humidity running performance of proton exchange membrane fuel cell
CN110380060A
Fuel cell catalyst layer and fuel cell
CN114361469A
Cited By
Catalyst for low-humidity fuel cell as well as preparation method and application of catalyst
CN121355280A
Proton exchange membrane electrode, preparation method thereof and proton exchange membrane fuel cell
CN121726422A
Preparation method of bionic self-capturing water membrane electrode of proton exchange membrane fuel cell
CN122532260A